Method for manufacturing pressure-bonded sheet and image forming apparatus

By controlling the solubility parameter, viscoelastic properties, and particle size differences between toner and adhesive, the method addresses peeling offset issues in pressure-bonded postcards, ensuring strong adhesion and easy separation, enhancing image quality and glossiness.

JP7600194B2Active Publication Date: 2024-12-16CANON KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022147741
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-09-16
Publication Date
2024-12-16
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

Existing pressure-bonded postcard printers face issues with peeling offset, where toner printed on paper peels off with the adhesive, due to inappropriate physical properties and conditions of toner and glue, leading to poor adhesion and separation difficulties.

Method used

A method and apparatus that control the solubility parameter (SP value), viscoelastic properties, and particle size differences between toner and adhesive to prevent mixing and ensure proper adhesion and separation, involving specific materials and processing steps like laminating an adhesive layer, fixing, overlapping, and crimping under controlled temperature and pressure.

Benefits of technology

The method effectively suppresses peeling offset, ensuring the postcards maintain adhesive strength while allowing easy separation, improving image quality and glossiness of the peeled surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600194000006
    Figure 0007600194000006
  • Figure 0007600194000007
    Figure 0007600194000007
  • Figure 0007600194000008
    Figure 0007600194000008
Patent Text Reader

Abstract

To provide a crimped sheet manufacturing method that prevents peeling offset occurring when a crimped postcard is opened, while using an image forming apparatus that can perform print processing and crimping processing in a series of events, and the image forming apparatus.SOLUTION: A crimped sheet manufacturing method for manufacturing a crimped sheet in which sheets are crimped in a peelable state includes: a step of forming, on a sheet, a composite layer obtained by laminating an adhesive layer formed by using a powder adhesive as a surface layer on a toner image formed by using printing toner; a fixing step of heating the composite layer formed on the sheet to fix the composite layer to the sheet; a step of superimposing, in an opposed state, an area on the sheet where the composite layer is fixed and an area on a sheet identical to the sheet or a sheet different from the sheet where another composite layer is fixed; and a crimping step of applying pressure to the superimposed sheets under heating to crimp the sheets. A difference in a solubility parameter (SP value) between the printing toner and the powder adhesive is 1.0 (cal / cm3)1 / 2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a pressure-sensitive sheet such as a pressure-sensitive postcard, and an image forming apparatus having a means for manufacturing a pressure-sensitive sheet. [Background technology]

[0002] Sealed postcards that seal confidential information such as invoices and pay slips need to have a certain adhesive strength to prevent them from coming off during delivery, but at the same time, it is important that they can be easily peeled off so that they can be opened after arriving at the user's hands. Furthermore, the printer that creates the above-mentioned laminated postcards is extremely convenient because it is simple and space-saving: it prints letters and images on a paper medium (hereinafter referred to as paper), and then transports the paper as is, folds it, and laminates it to create the laminated postcards. It is desirable for such a printer to have a simple configuration in which a process cartridge filled with a developer for printing (hereafter referred to as toner) and a powder adhesive for lamination (hereafter referred to as glue) is mounted in the same printer body, and printing is performed using a conventional electrophotographic image formation process, while a folding unit and a lamination unit can be added to handle both printing and lamination. However, problems arise when two different types of powder are used in a series of image formation processes. Specifically, if the physical properties and conditions of the toner and glue are not optimized, they will dissolve or mix with each other, and when a sealed postcard in which glue 2 and toner 8 are sealed with folded paper 4 is opened as shown in Fig. 2A, the toner printed on paper 4 may peel off together with glue 2, as shown in Fig. 2B, resulting in the toner 8 being transferred to the white background of the opposite side (hereinafter referred to as peeling offset). As for the material of this adhesive, Patent Document 1 clearly states that a hydrocarbon resin (such as polyethylene) is suitable. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-45861 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, in regard to the problem of peeling offset, the adhesive regulations in Patent Document 1 alone are insufficient for the manufacture of pressure-bonded postcards, which involve a series of printing and pressure-bonding processes, and for printers. It is necessary to select the material, type, form, etc. of both, including the toner, based on their physical properties. In view of the above situation, the present invention aims to propose an effective method for manufacturing a pressure-bonded sheet and an image forming apparatus that uses an image forming apparatus that can perform printing and pressure-bonding processes in a single flow, while suppressing the peeling offset that occurs when a pressure-bonded postcard is opened. [Means for solving the problem]

[0005] The above object can be achieved by using the following configuration. That is, the present invention is a method for manufacturing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable state, Formed using printing toner Unestablished An adhesive layer formed using a powder adhesive was laminated on the toner image as a surface layer. Unestablished forming a composite layer on the sheet; a fixing step of heating the composite layer formed on the sheet to fix it to the sheet; a step of overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; a compression bonding step of applying pressure to the overlapping portion of the composite layer and the other composite layer under heat; having The difference in solubility parameter (SP value) between the printing toner and the powder adhesive is 1.0 (cal / cm 3 ) 1 / 2 The present invention relates to a method for producing a pressure-bonded sheet, characterized in that:

[0006] The present invention also provides an image forming apparatus for manufacturing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable manner, comprising: Formed using printing toner Unestablished An adhesive layer formed using a powder adhesive was laminated on the toner image as a surface layer. Unestablished means for forming a composite layer on the sheet; a fixing means for heating the composite layer formed on the sheet to fix it to the sheet; a means for overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; and a bonding means for bonding the composite layer and the other composite layer by applying pressure under heat to the overlapping portion of the composite layer; having The difference in solubility parameter (SP value) between the printing toner and the powder adhesive is 1.0 (cal / cm 3 ) 1 / 2 The present invention relates to an image forming apparatus characterized by the above.

[0007] The present invention also provides a method for producing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable manner, comprising the steps of: Formed using printing toner Unestablished An adhesive layer formed using a powder adhesive was laminated on the toner image as a surface layer. Unestablished forming a composite layer on the sheet; a fixing step of heating the composite layer formed on the sheet to fix it to the sheet; a step of overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; a compression bonding step of applying pressure to the overlapping portion of the composite layer and the other composite layer under heat; having The printing toner contains a wax, When the storage modulus of the printing toner at the temperature in the fixing step is G'(A1), the storage modulus of the printing toner at the temperature in the pressure bonding step is G'(A2), the storage modulus of the powder adhesive at the temperature in the fixing step is G'(B1), and the storage modulus of the powder adhesive at the temperature in the pressure bonding step is G'(B2), G'(A1)>G'(A2) G'(B1)>G'(B2) G'(B1)>G'(A1) Fulfilling This relates to a method for manufacturing a pressure-bonded sheet, characterized in that the temperature in the fixing step is a temperature between the start point onset temperature and the end point onset temperature of the change region caused by melting in the storage elastic modulus curve of the powder adhesive.

[0008] The present invention also provides a method for producing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable manner, comprising the steps of: Formed using printing toner Unestablished An adhesive layer formed using a powder adhesive was laminated on the toner image as a surface layer. Unestablished forming a composite layer on the sheet; a fixing step of heating the composite layer formed on the sheet to fix it to the sheet; a step of overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; a compression bonding step of applying pressure to the overlapping portion of the composite layer and the other composite layer under heat; having The method for producing a pressure-bonded sheet is characterized in that the difference in average particle size between the toner and the powder adhesive is less than 25 μm, and the powder adhesive has a broader particle size distribution or a larger half-value width than the toner.

[0009] Furthermore, the present invention provides an image forming apparatus for manufacturing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable state, comprising: Formed using printing toner UnestablishedAn adhesive layer formed using a powder adhesive was laminated on the toner image as a surface layer. Unestablished means for forming a composite layer on the sheet; a fixing means for heating the composite layer formed on the sheet to fix it to the sheet; a means for overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; and a bonding means for bonding the composite layer and the other composite layer by applying pressure under heat to the overlapping portion of the composite layer; having The toner and the powder adhesive have an average particle size difference of less than 25 μm, and the powder adhesive has a broader particle size distribution or a larger half-value width than the toner. Effect of the Invention

[0010] By adopting the configuration of the present invention, in an image forming apparatus that can perform printing and bonding processes in a single flow, it is possible to make the printing toner and the powder adhesive (glue) less compatible with each other or less likely to mix with each other, thereby suppressing the occurrence of peeling offset when the bonded postcard is opened. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing an example of an image forming apparatus according to the present invention. [Diagram 2] 2A and 2B are diagrams illustrating the peel offset phenomenon. [Diagram 3] FIG. 3 is an explanatory diagram showing viscoelastic properties in the examples of the present invention and the comparative examples. [Figure 4] FIG. 4 is an explanatory diagram showing the temperatures during fixing and pressure bonding in addition to the viscoelastic properties in the examples of the present invention and the comparative examples. [Diagram 5] FIG. 5 is an explanatory diagram showing the temperature and viscoelasticity characteristics of the developer (toner) and powder adhesive (glue) during fixing and compression in an embodiment of the present invention. [Figure 6]FIG. 6 is an explanatory diagram showing the temperature and viscoelasticity characteristics when the powder adhesive (glue) is fixed in an embodiment of the present invention. [Figure 7] FIG. 7 is an explanatory diagram showing the temperature and viscoelasticity characteristics during fixing of the developer (toner) and the powder adhesive (glue) in an embodiment of the present invention. [Figure 8] FIG. 8 is an explanatory diagram showing the temperature and viscoelastic properties of the future developer (toner) and powder adhesive (glue) during fixing and pressing in an embodiment of the present invention, as well as the viscoelastic properties of the future developer (toner). [Figure 9] Figures 9A, 9B and 9C are schematic diagrams showing an image forming apparatus in an embodiment of the present invention, the contact state between the image carrier (drum) and intermediate transfer belt (ITB) at the 1st station, and the contact state between the image carrier (drum) and intermediate transfer belt (ITB) at the 2nd station. [Figure 10] 10A and 10B are schematic diagrams showing the states immediately before and after contact between the image carrier (drum) and intermediate transfer belt (ITB) of the 2nd station when there is an average particle size difference in an embodiment of the present invention. [Figure 11] 11A and 11B are schematic diagrams showing the state of a pressure-bonded postcard before and after peeling when there is a difference in average particle size in an embodiment of the present invention. [Figure 12] 12A and 12B are schematic diagrams showing the state immediately before and after contact between the image carrier (drum) and intermediate transfer belt (ITB) at the 2nd station when there is a difference in average particle size and the particle size distribution is wide in an embodiment of the present invention. [Figure 13] 13A and 13B are schematic diagrams showing the state of a pressure-bonded postcard before and after peeling when there is a difference in average particle size and a wide particle size distribution in an embodiment of the present invention. [Figure 14] 14A and 14B are diagrams showing the average particle size and particle size distribution in an example of the present invention. [Figure 15] 15A and 15B are schematic diagrams showing the gaps between particles of developer (toner) and powder adhesive (glue) in an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <Overall overview of the device> The method for producing a pressure-bonded sheet and the image forming apparatus of the present invention, which produce a pressure-bonded sheet in which sheets are bonded to each other in a peelable state, are based on the steps (or means) of: (i) forming a composite layer on a sheet by laminating an adhesive layer formed as a surface layer using a powder adhesive on a toner image formed using a printing toner; (ii) a fixing step of heating the composite layer formed on the sheet to fix it to the sheet; (iii) overlapping an area of ​​the sheet on which the composite layer has been formed and fixed with an area of ​​the sheet on the same sheet or on a different sheet on which another composite layer has been fixed; and (iv) a bonding step of bonding the overlapping portion of the composite layer and the other composite layer by applying pressure under heat. It is.

[0013] Here, in step (iii), when "different sheets" are overlapped with each other, the operation of folding the sheets is not necessarily required. However, when "same sheets" are overlapped with each other, the operation of folding the sheets is required. Therefore, for the sake of convenience, the above step (iii) is referred to as a "folding step", and the means for this step may be referred to as a "folding means" or a "folding unit".

[0014] FIG. 1 is a schematic cross-sectional view showing an example of an image forming apparatus according to the present invention, which is configured by adding a folding unit 6 and a pressing unit 7 to a conventional full-color image forming apparatus.

[0015] The process cartridge filled with the adhesive 2 is mounted in the most upstream station of the four image forming stations, and the other stations are equipped with process cartridges of the colors yellow (hereinafter referred to as Y), magenta (hereinafter referred to as M), and cyan (hereinafter referred to as C). However, the configuration is not limited to the above. Specifically, the order and ratio of the number of process cartridges of each color of adhesive or toner mounted in each station, such as monochrome, can be set arbitrarily according to needs. It should also be noted in advance that the number of stations is not limited to four.

[0016] Next, the image formation process (charging, developing, transferring, fixing) used to create laminated postcards, as well as the flow of the folding and laminating processes, will be described in detail.

[0017] (Explanation of the image formation process, folding process, and bonding process) In the image forming apparatus of FIG. 1, each station has an image carrier (hereinafter referred to as drum) 1 with an OPC photosensitive layer (organic photoconductor), which can rotate in the direction of the arrow at a predetermined process speed. The surface of the drum 1 is charged to a predetermined polarity and potential by a charging roller 12 to which a charging bias is applied, and then receives an exposure beam from a laser beam scanner 16 to form an electrostatic latent image. Then, for the electrostatic latent image, a powder adhesive (hereinafter referred to as glue) 2 is transported from a developer container to a developer carrying member 17, and the glue 2 is transferred to the drum 1 by a developing means (contact charging and developing bias), i.e., the electrostatic latent image is developed.

[0018] Next, the glue on the drum 1 is (primarily) transferred to an intermediate transfer belt (hereinafter referred to as ITB) 3 that comes into contact with the drum by a predetermined transfer pressure and transfer bias from a transfer roller 14, and the glue 2 on the ITB 3 is carried to the next station. In addition, a portion of the glue 2 on the drum that was not transferred is scraped off with a cleaning blade or the like, and then the drum 1 is charged, exposed, and developed again, allowing repeated image formation. The scraped off glue 2 is then stored and collected in a cleaning container 13. The components that perform this series of processes (drum 1, charging roller 12, developing container 2, cleaning container 13) are integrated into a cartridge called a process cartridge, and four process cartridges, each containing a different powder, are lined up and housed in the main body.

[0019] In the next station, the same process is followed, but this time Y toner (yellow toner) 8 is transferred from the drum 11 to the ITB. The transfer is then repeated in sequence from the next station onwards, resulting in at least two layers of powder (glue and toner of one other colour, up to a maximum of glue, Y toner 8, M toner (magenta toner) 9 and C toner (cyan toner) 10) being stacked in order on the ITB. Then, the toner image is (secondarily) transferred from the ITB 3 to the paper 4 by the transfer bias of the secondary transfer roller 15 for the conveyed recording material (hereinafter referred to as paper) 4. As a result, the stacking order is reversed on the paper 4 from the ITB 3, and a composite layer is formed in which the glue is stacked on top of the toner image, so that the papers 4 can be stacked facing each other and pressed together with the glue. For this reason, in a device using an intermediate transfer member such as an intermediate transfer belt, it is desirable to install the glue in the most upstream station in image formation.

[0020] The adhesive is then heated and pressurized by the fixing unit 5, melting it together with the toners 8, 9, and 10, and is fixed onto the paper 4. At this time, it is important that most of the adhesive 2 is fixed in a moderately softened state while still melting. The reason for this is that if the toners 8, 9, and 10 and the adhesive 2 are all melted at once during fixing, they will be easily mixed together, and the peel-off offset properties will be reduced, so the present invention is devised in the following examples.

[0021] The paper is then sent to the folding unit 6, where it is folded into a specified shape, and then heat-bonded by the bonding unit 7 under pressure to create a bonded postcard. During bonding, it is important to perform the bonding at a temperature that melts the glue in order to maintain the adhesive strength of the bonded postcard while suppressing peel offset.

[0022] The reason why both the glue and the toner are not melted at once during fixing, but are melted during pressing, is as follows: By fixing only to the extent that the glue does not melt completely during fixing but only softens, the heat transfer to the glue during pressing is slower than that to the toner. This creates a difference in the ease with which the two melt, making it difficult for them to dissolve at their interface, or the toner layer that has melted once during fixing has wax on its surface, which acts as a wall that makes it difficult for the glue to dissolve in the toner layer, making it difficult for the two to dissolve in each other.

[0023] <Explanation of peeling offset and its causes> The laminated postcard created through the above process is delivered to the user and then opened. However, as mentioned above, peel offset may occur depending on the physical properties of the toner and adhesive and the conditions.

[0024] As a result of investigating the melting state and compatibility of printing toner and paste, the present inventors have found that 1. Difference in solubility parameter (SP value) between toner and glue 2. Difference in viscoelastic properties between toner and glue It was found that good peelability could be obtained by controlling either of the above.

[0025] In addition, the powder characteristics of the toner and glue were examined. 3. Differences in average particle size and particle size distribution between toner and glue It was found that good peelability could be obtained by controlling

[0026] The three control points will be explained in turn below.

[0027] (About toner and glue) Before describing the three factors that contribute to the peel offset, the toner and adhesive according to the present invention will be described.

[0028] The toner used in the present invention contains a thermoplastic binder resin such as styrene acrylic resin, polyester resin, vinyl resin, or acrylic resin, and further contains wax, colorant, external additive, charge control agent, magnetic material, etc., as necessary. The shape of each toner particle is spherical or amorphous, and the average particle size is about 6 μm±2 μm. However, the material and physical properties are not limited to the above. In particular, in order to suppress the occurrence of peeling offset, the material and physical properties (structure) of the toner may be changed to match the material and physical properties of the glue, and a toner with a different SP value, viscoelasticity characteristics, average particle size, and particle size distribution may be used.

[0029] On the other hand, the paste is preferably made of powder particles of polyethylene. The powder particles of polyethylene can be produced by a polymerization method or a pulverization method, and an external additive may be added to the surface. The shape of each particle is spherical or amorphous, and the average particle size is about 6 to 30 μm. However, the material and physical properties are not limited to the above. In particular, in order to suppress the occurrence of peeling offset, the material and physical properties (structure) of the paste may be changed according to the material and physical properties of the toner, and a paste with a different SP value, viscoelasticity, average particle size, and particle size distribution may be used.

[0030] [Example 1] (1. Difference in solubility parameter (SP value) between toner and glue) As mentioned above, the level of peeling offset varies depending on the compatibility and mixing condition of the toner and the adhesive. Therefore, it is necessary to form an image and create a pressure-bonded postcard when the toner and the adhesive are poorly compatible or poorly mixed.

[0031] Therefore, we focused on an index called the SP value, which indicates the compatibility of two types of materials. The SP value indicates the solubility of the two target substances and is a unique value determined by the material and molecular structure. In addition, two different substances have characteristics in that if their SP values ​​are far apart, they are less compatible, and if their SP values ​​are close, they are more compatible. Next, we will explain how to calculate the SP value.

[0032] (How to calculate solubility parameter (SP value)) The SP value in the present invention was calculated using the following Fedors formula. The values ​​of Δei and Δvi here were based on the evaporation energy and molar volume (25°C) of atoms and atomic groups in Tables 3-9 of "Basic Science of Coatings" pp. 54-57, 1986 (Maki Shoten). Ev is the evaporation energy, V is the molar volume, Δei is the evaporation energy of the atom or atomic group of the i component, and Δvi is the molar volume of the atom or atomic group of the i component. For example, a substance called hexanediol is composed of atomic groups (-OH) x 2 + (-CH2) x 6, and the SP value is calculated using the following exemplary formula, and the SP value (δi) is 11.95. SP value calculation formula δi=[Ev / V] 1 / 2 = [Δei / Δvi] 1 / 2 Example) SP value of hexanediol δi=[Δei / Δvi] 1 / 2 =[{(5220)×2+(1180)×6} / {(13)×2+(16.1)×6}] 1 / 2 =11.95

[0033] In this specification, the unit of SP value is (cal / cm 3 ) 1 / 2 However, (cal / cm 3 ) 1 / 2 =0.48888×(J / cm 3 ) 1 / 2 It is.

[0034] In this specification, the SP value of the toner is the SP value of the binder resin.

[0035] In this embodiment, the toner used had the following formulation. The binder resin was changed to that shown in Table 1 below. Note that "parts" refers to "parts by mass."

[0036] (Example of printing toner production) Next, a method for producing the printing toners Ty, Tm, and Tc will be illustrated. First, the following materials were prepared. Styrene 60.0 parts Colorant 6.5 parts (CI Pigment Blue 15:3, Dainichi Seika Chemicals Co., Ltd.) The above materials were placed in an attritor (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and further dispersed using zirconia particles having a diameter of 1.7 mm at 220 rpm for 5 hours to obtain a pigment dispersion liquid.

[0037] In addition, the following materials were prepared: Styrene 15.0 parts n-Butyl acrylate 25.0 parts Polyester resin 4.0 parts (Weight average molecular weight (Mw) 20,000, glass transition temperature (Tg) 75°C, acid value 8.2mgKOH / g) Behenyl behenate 12.0 parts Divinylbenzene 0.5 parts The above materials were mixed and added to the pigment dispersion liquid. The resulting mixture was kept at 60° C. and stirred at 500 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to dissolve and disperse uniformly, thereby preparing a polymerizable monomer composition.

[0038] Meanwhile, 850.0 parts of 0.10 mol / L-Na3PO4 aqueous solution and 8.0 parts of 10% hydrochloric acid were added to a container equipped with a high-speed stirring device Clearmix (manufactured by M Technique Co., Ltd.), the rotation speed was adjusted to 15,000 rpm, and the temperature was heated to 70°C. 127.5 parts of 1.0 mol / L-CaCl2 aqueous solution were added to this to prepare an aqueous medium containing a calcium phosphate compound.

[0039] After the polymerizable monomer composition was added to the aqueous medium, 7.0 parts of t-butyl peroxypivalate, a polymerization initiator, was added, and the mixture was granulated for 10 minutes while maintaining a rotation speed of 15,000 rpm. After that, the high-speed agitator was replaced with a propeller agitator, and the mixture was reacted at 70°C for 5 hours under reflux, and then the liquid temperature was increased to 85°C and the mixture was reacted for another 2 hours.

[0040] After the polymerization reaction was completed, the resulting slurry was cooled, and then hydrochloric acid was added to the slurry to adjust the pH to 1.4 and the slurry was stirred for 1 hour to dissolve the calcium phosphate salt.The slurry was then washed with three times the amount of water, filtered, dried, and classified to obtain toner particles.

[0041] Thereafter, silica fine particles (number average particle diameter of primary particles: 10 nm, BET specific surface area: 170 m) that had been hydrophobized using dimethyl silicone oil (20% by mass) were added to 100.0 parts of the toner particles as an external additive. 2 2.0 parts of silica fine particles (1.0 parts / g) were added. The toner particles to which the silica fine particles were added were mixed at 3000 rpm for 15 minutes using a Mitsui Henschel mixer (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain a toner (printing toner). The weight average particle diameter of the obtained toner was about 6 μm.

[0042] Next, in order to investigate the compatibility of these toners with glue (powder adhesive), several glues with different resin types shown in Table 1 were used, and the image formation process described above was carried out. Test samples of the following pressure-bonded postcards were then created, and the peel offset was checked.

[0043] The test samples were prepared by printing two types of toner - glue and one of the colors Y, M or C - all over the inside of a 3cm x 4cm area of ​​a strip of paper (Canon GF-C081) prepared as a substitute for a pressure-sensitive postcard, and one printed entirely with glue and one printed entirely with glue alone, then stacking them with the printed sides facing inwards, fusing and pressing them together to create the samples. In this experiment, the process conditions for image formation (applied bias, settings for each component, temperature conditions, etc.) were set to be almost the same for the glue and toner, but they may be set separately for each powder. In the test described below, when high-density polyethylene was used as the glue, the fusing and pressing temperatures were raised to perform fusing and pressing.

[0044] The peel test was carried out using a tensile tester, TENSILON, Model: RTG-1255, manufactured by ORIENTEC Co., Ltd., by clamping both ends of the strip to the test device and peeling at a pulling speed of 50 mm / min.

[0045] Regarding the occurrence of peeling offset, the peeled surface of the strip peeled off with TENSILON was checked to determine whether or not the toner was transferred to the strip on which only the glue was printed. The results are explained below with reference to Table 1.

[0046] As shown in Table 1, when the toner and glue are made of the same polyester resin, the SP value for both is 9.30 because they are the same material. When a test sample was created in this state and a peel test was performed, the peeling surfaces became miscible with each other, and peel offset occurred as they did not separate well. It was also confirmed that when the toner and glue were both made of the same styrene acrylic resin, they became miscible with each other and peel offset occurred.

[0047] Next, the toner was changed to polyester resin and the adhesive to polypropylene resin with a similar SP value, and a peeling test was conducted. The results confirmed that the toner and adhesive were compatible and did not separate well. Therefore, it was found that the ease of compatibility was due to the similar SP values, not the material.

[0048] Next, we will explain the case where the difference in SP value is large. This time, we performed the same test using two polyethylenes with different structures, namely low-density polyethylene and high-density polyethylene, as the glue. The SP value of low-density polyethylene was 7.93 (the difference in SP value with the polyester contained in the toner was 1.37), and the SP value of high-density polyethylene was 8.29 (the difference in SP value with the polyester contained in the toner was 1.01). As a result, it was found that the separation surfaces of both polyethylenes were not compatible with each other, and the peeled surfaces were cleanly separated and peeled off in a smooth and glossy state. Therefore, it was found that if the difference in SP value is at least 1.0 or more, it is possible to suppress compatibility with each other. In addition, low-density polyethylene allows image formation under almost the same process conditions as toner, and in this respect it is preferable to high-density polyethylene.

[0049] [Table 1]

[0050] The above are the test results regarding the SP value, but next we carried out a model experiment to examine the peel offset under conditions outside the range of normal use, changing the toner and adhesive materials from the above combination. The purpose of this model experiment is as follows:

[0051] The first is to investigate whether compatibility can be suppressed even if the difference in SP values ​​is less than 1.0, i.e., to investigate how much margin there is, for example, whether 1.0 is an appropriate value, and the second is to investigate whether the threshold value of a difference in SP values ​​of 1.0 is a condition that can only be achieved with the combination of the above-mentioned polyester resin for the toner and the polyethylene resin for the adhesive, i.e., to investigate whether the same results can be obtained with other combinations.

[0052] The model experiment will be explained in detail. In this model experiment, the amount of toner and glue on the strip mentioned above was made uneven so that peeling offset would occur easily. By making the coat uneven, the toner would not bond to the surrounding toner when it melted (the toner would be more likely to become isolated), and it would peel off easily from the paper.

[0053] Therefore, in this model experiment, when the toner and adhesive have the same SP value, the peel offset worsens. The results are shown in Table 2.

[0054] First, the above model experiment was carried out using polyester resin toner and low-density polyethylene and high-density polyethylene as glue as shown in Table 2. In the case of high-density polyethylene, where the difference in SP value was 1.01, slight peeling offset occurred. On the other hand, in the case of low-density polyethylene, where the difference in SP value was 1.37, no peeling offset occurred.

[0055] In addition, when the toner was styrene acrylic resin and the glue was low-density polyethylene and high-density polyethylene, both normal peeling offset tests and model experiments were conducted. The difference in SP value between the toner and glue was 1.47 and 1.11, respectively, and when normal peeling tests and model experiments were conducted under these conditions, it was found that no peeling offset occurred for either low-density polyethylene, which had a difference in SP value of 1.47, or high-density polyethylene, which had a difference in SP value of 1.11.

[0056] Therefore, it was revealed that good results could be obtained if the difference in SP value for suppressing peel offset was 1.0 or more, and more preferably, the difference in SP value was 1.1 or more.

[0057] [Table 2]

[0058] [Example 2] (2. Difference in viscoelastic properties between toner and glue) Next, the viscoelastic property, which is another factor in the peel offset, will be described. The reason for focusing on this viscoelastic property will be described later.

[0059] From the viewpoint of viscoelastic properties, in the present invention, when the storage modulus of the toner at the temperature in the fixing process is G'(A1), the storage modulus of the toner at the temperature in the pressure bonding process is G'(A2), the storage modulus of the adhesive at the temperature in the fixing process is G'(B1), and the storage modulus of the adhesive at the temperature in the pressure bonding process is G'(B2), G'(A1)>G'(A2) G'(B1)>G'(B2) G'(B1)>G'(A1) and the temperature in the fixing step must be between the start and end onset temperatures of the change region caused by melting in the storage elastic modulus curve of the glue.

[0060] Here, the viscoelastic property is an index showing the energy stored in the powder for a given strain, and is expressed as the storage modulus with respect to temperature. In the case of powder such as thermoplastic resin as in this embodiment, when the toner or glue is heated and the temperature is increased, the viscoelastic property changes and the storage modulus becomes smaller. This state indicates that the toner or glue has melted and become soft (hereinafter referred to as softened).

[0061] If the glue is close to being a single material, the softening temperature will be close to the melting point, and the viscoelasticity will tend to change suddenly around that temperature range. However, if it contains multiple materials, such as toner, the range in which the viscoelasticity changes differs for each substance, so there tends to be fewer areas where the viscoelasticity changes suddenly, and the viscoelasticity changes gradually depending on the heating temperature. Next, we will explain how to measure the viscoelastic properties of toner and glue.

[0062] (Measurement of viscoelastic properties and storage modulus of toner and glue) The viscoelastic properties of the toner and glue, that is, the storage modulus, were measured using a DMA8000 (Perkin Elmer), a compression fixture (product number: N533-0320), and a heating furnace (product number: N533-0267). First, as a measurement sample, a tablet molder (e.g., NT-100H, NPA Systems) was used in an environment of 25°C to pressure-mold (compression-mold at about 10 MPa for about 60 seconds) the toner or glue (about 2.0 g) into a disk shape with a diameter of 7.9 mm and a thickness of 2.0±0.3 mm to create a sample, which was measured while being heated, and a graph of the storage modulus versus heating temperature was created.

[0063] In this embodiment, the toner used in the measurement of viscoelasticity was the same as that used in the first embodiment in terms of the components, manufacturing process, particle size, etc.

[0064] That is, the toner uses a styrene acrylic resin as a binder resin, contains wax as a release agent, and uses polyethylene as a glue, but the materials of the toner and glue are not limited to these. In particular, it is sufficient if the toner and glue are made of materials with different viscoelastic properties, and if the storage modulus of the glue is higher than that of the toner at least at the fixing temperature, peeling offset can be suppressed, so the materials of the toner and glue are not limited to these.

[0065] The measurement results of viscoelasticity are shown in Figure 3. The horizontal axis shows the temperature at which the powder was heated under specified conditions, and the vertical axis shows the storage modulus of each powder at that time. It was found that the viscoelastic properties of each of the three powders showed the following trends.

[0066] The toner shown by the solid line is hard at low temperatures due to its high storage modulus, but as the temperature increases, the storage modulus gradually decreases and the toner tends to soften almost linearly.

[0067] On the other hand, the paste shown by the dashed line was softer than the toner before heating, but its storage modulus hardly changed up to a certain temperature, and it showed the characteristic of suddenly softening at temperatures approaching the melting point.

[0068] However, there are low-density polyethylene and high-density polyethylene, which have different structures: low-density polyethylene, shown by the dashed line, has a higher branched structure than high-density polyethylene, shown by the dotted line, and therefore has a lower melting point. Therefore, it softens at a lower temperature, whereas high-density polyethylene has a predominantly linear molecular structure, and therefore has a higher melting point and softening temperature.

[0069] (Improvement of peeling offset by viscoelastic properties) As mentioned above, the level of peeling offset varies depending on the compatibility and mixing condition of the toner and the adhesive. Therefore, it is necessary to form an image and create a pressure-bonded postcard when the toner and the adhesive are poorly compatible or poorly mixed.

[0070] Therefore, we focused on an index called viscoelasticity, which indicates how easily a material softens. When actually creating a pressure-bonded postcard, there are two heating timings: fixing and pressure bonding. By using these two temperatures and the difference in viscoelasticity between the toner and glue, we found that it is possible to improve peel offset by creating a situation in which they are less compatible with each other. Next, we will explain the specific viscoelasticity characteristics that we obtained this time.

[0071] Fig. 4 shows the actual paper temperature during fixing and during pressing (i.e. the temperature of the toner and glue on the paper) added to Fig. 3. The paper temperature during fixing is shown by vertical solid line A, and the paper temperature during pressing is shown by vertical solid line B. In this embodiment, the temperature during pressing B was set higher than the temperature during fixing A.

[0072] The viscoelastic properties of each powder during fixing A are explained below. During fixing A, the toner was almost completely melted, and the low-density polyethylene, which acts as a glue, was slightly melted. However, the high-density polyethylene was hardly melted at all.

[0073] Next, the viscoelastic properties of each powder at compression time B will be explained. At compression time B, it was found that while the toner and low-density polyethylene were almost melted, the high-density polyethylene was not melted and could not be fixed. In this embodiment, since the glue was fixed at the same temperature setting as the toner, it is desirable to use low-density polyethylene for the glue, rather than high-density polyethylene, which does not fix easily. Therefore, from here on, we will use low-density polyethylene for the glue and explain how to suppress peeling offset.

[0074] Figure 5 is a graph that uses black and white circles to show the storage modulus of the toner and the storage modulus of the glue (low-density polyethylene) at the temperatures during fixing and pressing, making it easy to explain the relationship between viscoelastic properties and peel offset. Figure 5 shows the fixing of the glue as (1), the pressing of the glue as (2), the fixing of the toner as (3), and the pressing of the toner as (4) in a simple and easy-to-understand way. It was found that the suppression of peel offset is improved in the following three states, which will be explained in order.

[0075] The first reason is that, as shown in FIG. 5, in this embodiment, the paper temperature during pressing is set higher than that during fixing, so the viscoelasticity is in the order of (1)>(2) and (3)>(4).

[0076] Secondly, as shown in Figure 6, the adhesive does not need to melt completely when fixed, but can be pressed by melting when pressed, so (1) can be used when it is slightly softened and beginning to melt. In other words, (1) should be within the softening region of the viscoelastic properties as shown in Figure 6.

[0077] The third condition is considered to be the most important condition for suppressing peel offset, and it is to satisfy the relationship (1)>(3) at the temperature of fixation A as shown in Figure 7. Here, the difference between the storage modulus of (1) and (3) at the temperature of fixation A is |Log10(1×10 5 )-Log10(3×10 4 )|And |Log10(3×10 6 )-Log10(6×10 4 )| or less.

[0078] The reason for this is that if the viscoelastic properties of the toner and glue are similar and both powders melt at once during fixing, they will become more compatible, and it was found that they are already compatible enough to cause peeling offset when fixing is complete. Therefore, in order to improve peeling offset, it is necessary to fix the glue only slightly softened without completely melting it during fixing. In other words, by fixing the glue in a slightly softened state during fixing, it is possible to make the entire glue melt only when it is pressed against the paper. In other words, the two powders do not become molten during fixing, creating a situation in which they are less likely to become compatible, and peeling offset can be improved.

[0079] Also, depending on the type of toner, by mainly melting the toner during fixing, a wax layer can be formed on the toner surface in a state in which it is incompatible with the adhesive. This acts as a wall of toner that is difficult to dissolve in the adhesive when pressed, thereby suppressing compatibility.

[0080] Regarding the temperature and pressure conditions during bonding, if the temperature or pressure during the bonding process is too high, peeling offset is more likely to occur, so the conditions for bonding should be a paper temperature of approximately 105°C to 115°C, a paper speed of 100 mm / s, and a pressure of 32 kg (one-sided load of 16 kg x 2).

[0081] From the above, it was found that in order to improve the peel offset due to viscoelastic properties, it is sufficient to satisfy the following relationships: viscoelasticity of the glue at the time of fixing > viscoelasticity at the time of pressing ((1) ≧ (2)), viscoelasticity of the toner at the time of fixing > viscoelasticity at the time of pressing ((3) ≧ (4)), the viscoelasticity of the glue at the time of fixing ((1)) is within the range of the softening region in the viscoelastic properties, and the viscoelasticity of the glue at the time of fixing ≧ viscoelasticity of the toner ((1) ≧ (3)).

[0082] Furthermore, we also assumed that as toner material development advances in the future, the gradient of change in the viscoelastic properties of the toner (the gradient of the softening region) will become steeper than that of the glue. Figure 8 shows the assumed situation.

[0083] The solid line in Figure 8 shows the viscoelasticity of the toner, which is sharper melting (easier to soften) than the glue shown by the dashed line. Even if one were to try to change the positional relationship of (3) and (4), the position of (3) is inevitable because the toner itself melts when fixed, so it is expected that the positional relationship of (3) and (4) will always be as shown in Figure 8 (because it is a thermoplastic resin, the viscoelasticity of (4) is lower than that of (3)). In other words, it was found that the positional relationship of (1), (2), (3), and (4) will not change, even if the solid line part with a lower temperature than (3) changes.

[0084] From the above, if the above relationship is maintained, the adhesive can be fixed in a slightly softened state during fixing, and the entire adhesive can be melted only when it is pressed. This prevents the toner and adhesive from melting all at once during fixing, making it difficult for them to become compatible, which is expected to improve peel offset.

[0085] In this embodiment, the fixing temperature (temperature of the paper during fixing) was 95° C., and the pressing temperature (temperature of the paper during pressing) was 105° C. In addition, the storage modulus of the adhesive at the fixing temperature was 3×10 6 Pa, storage modulus at the adhesive pressure temperature is 2×10 4 Pa, and the storage modulus of the toner at the fixing temperature is 6×10 4 Pa, storage modulus of toner at compression temperature 2×10 4 It was Pa.

[0086] [Example 3] (3. Difference in average particle size and particle size distribution between toner and paste) As mentioned above, the level of peeling offset varies depending on the compatibility and mixing condition of the toner and adhesive. Therefore, it is necessary to form an image and create a pressure-bonded postcard when the toner and adhesive are poorly compatible or poorly mixed.

[0087] Therefore, we focused on the state in which the toner and adhesive exist as powder before fixing and pressing, and thought that peel offset could be suppressed by improving the state in which they are mixed together.

[0088] When the average particle size and particle size distribution of the toner and glue were varied, it was found that if the average particle size and particle size distribution of the toner and glue were the same, peeling offset did not occur even when a bonded postcard was made through a series of image formation processes and peeled off. However, it was found that peeling offset occurred significantly when the average particle size of the toner and glue was different and the average particle size of the glue was about 25 μm larger than that of the toner. On the other hand, it was found that the suppression of peeling offset was improved when the particle size distribution was wide (i.e., the half-width of the particle size distribution was large) or there were many particles smaller than the average particle size of the glue, even if the average particle size of the glue was about 25 μm larger than that of the toner. Therefore, the mechanism of this improvement is explained below and the necessary conditions are presented. The average particle size and particle size distribution were measured using the following method.

[0089] (Measuring average particle size and particle size distribution) The average particle size and particle size distribution of the toner and glue, i.e., the weight-average particle size, are calculated as follows. The measurement device used is a precision particle size distribution measurement device using the narrow hole electrical resistance method, the Coulter Counter Multisizer 3 (registered trademark product name, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube. The measurement conditions are set and the measurement data is analyzed using the accompanying dedicated software, Beckman Coulter Multisizer 3 Version 3.51 (manufactured by Beckman Coulter, Inc.). The measurement is performed with an effective measurement channel count of 25,000.

[0090] The electrolyte solution used for the measurement is made by dissolving special grade sodium chloride in ion-exchanged water to a concentration of 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter). Before performing the measurement and analysis, the dedicated software is set as follows. In the "Change Standard Measurement Method (SOM)" screen of the dedicated software, the total count number in the control mode is set to 50,000 particles, the number of measurements is set to 1, and the Kd value is set to the value obtained using "Standard particle 10.0 μm" (manufactured by Beckman Coulter). The threshold and noise level are automatically set by pressing the "Threshold / Noise Level Measurement Button". In addition, the current is set to 1600 μA, the gain to 2, the electrolyte is set to ISOTON II, and "Flush aperture tube after measurement" is checked. In the "Pulse to particle size conversion setting" screen of the dedicated software, the bin interval is set to logarithmic particle size, the particle size bin is set to 256 particle size bins, and the particle size range is set to 2 μm to 60 μm. The specific measurement method is as follows. (1) Pour 200 mL of electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture tube flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker. 0.3 mL of a solution of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made from a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion-exchanged water is added as a dispersant. (3) Prepare an ultrasonic disperser "Ultrasonic Dispersion SysTem TeTora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees, and has an electrical output of 120 W. Place 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank, and add 2 mL of Contaminon N to this tank. (4) Set the beaker (2) in the beaker fixing hole of the ultrasonic disperser and operate the ultrasonic disperser. Then, adjust the height of the beaker so that the resonance state of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, add 10 mg of toner or glue to the electrolyte solution in small amounts and disperse it. Then, continue ultrasonic dispersion for another 60 seconds. During ultrasonic dispersion, adjust the water temperature in the water tank appropriately so that it is between 10°C and 40°C. (6) Using a pipette, drip the electrolytic solution (5) in which the toner or powder adhesive has been dispersed into the round-bottom beaker (1) placed in the sample stand to adjust the measurement concentration to 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using dedicated software provided with the device to calculate the weight average particle diameter.

[0091] (Identifying where toner and glue mix) Next, in a state where the above-mentioned peel offset occurs, the location where the toner and the adhesive are mixed is identified.

[0092] In the image formation process, the toner and glue exist in powder form in the development process, which transfers the developer from the developer carrying member to the drum, the primary transfer process, which transfers the developer from the drum to the ITB, and the secondary transfer process, which transfers the developer from the ITB to the paper. We then tried to identify the source of the problem by forcibly stopping the main body drive, and found that it was occurring in the primary transfer process, as shown in Figure 9C. In this process, both glue 2 and toner 8 are transferred onto the ITB 3, and they are mixed at this stage.

[0093] Figure 10A is a schematic diagram of the state before transfer pressure is applied, and the toner and glue are regularly carried on the drum according to the print pattern. However, when transfer pressure is applied, glue particles about 25 μm larger than the toner disrupt the toner image on the drum as shown in Figure 10B, and it was confirmed that the toner gets into the gaps between the larger glue particles. This is thought to be because the larger particles are heavy and difficult to move, and the lighter smaller particles move and enter the gaps. If this state occurs on the ITB, when the secondary transfer to the paper is performed, a layer of glue is placed on top of the disrupted toner layer on the paper, and the particles are mixed together more. As a result, the toner is fixed in an isolated position different from the normal position during fixing as shown in Figure 11A, and when the paper 4 is peeled off after pressure bonding as shown in Figure 11B, the isolated toner is peeled off together with the glue, which was found to be the cause of the peeling offset.

[0094] On the other hand, when the average particle size of the toner and the glue is the same, there are many contact points between the layers at the time of mixing, and the transfer pressure can be absorbed by the surface, so the toner and glue are not disturbed on the ITB. Therefore, it is thought that peeling offset does not occur.

[0095] In addition, when the average particle size of the glue is about 25 μm larger than that of the toner and there are many particles smaller than the average particle size of the glue (the glue has a wider particle size distribution than the toner, or the half-width of the particle size distribution is larger), small glue particles fill the gaps between the large glue particles on the ITB in advance as shown in FIG. 12A. Therefore, even when the toner is transferred from the drum to the ITB at the downstream station in image formation and transfer pressure is applied, the toner can be prevented from entering the gaps between the large glue particles as shown in FIG. 12B, so that mixing of the toner and glue on the ITB can be suppressed. In this way, the toner and glue do not mix with each other during fixing, and are fixed while maintaining their respective layers as shown in FIG. 13A. When the paper 4 is peeled off after pressing as shown in FIG. 13B, the toner and glue peel off without being disturbed at the interface between them, and peeling offset does not occur.

[0096] In addition to the above combinations of toner and glue, other combinations such as those shown in Table 3 are also possible. Table 3 shows that peel offset occurs when a combination of a small average particle size of toner and a large average particle size of glue is used, and that peel offset suppression is better with a large particle size distribution than with a small particle size distribution. In particular, it can be seen that the effect of a large particle size distribution of glue is large.

[0097] However, since the data in parentheses has a low contribution from peel offset, this embodiment will focus on combinations with a large particle size difference, namely, toner with a small average particle size (approximately 6 μm) and glue with small (approximately 6 μm) and large (approximately 30 μm) average particle sizes.

[0098] [Table 3]

[0099] Next, we will explain why peel offset suppression is improved by widening the particle size distribution of the glue. Figures 14A and 14B are graphs for the upper right corner of Table 3, that is, when the difference in average particle size and particle size distribution between the toner and glue is large. Figure 14A shows the glue with a large average particle size and large particle size distribution, while Figure 14B shows the toner with a small average particle size and small particle size distribution. In this case, since the particle size distribution of the glue is wide (i.e., the half-width of the particle size distribution is large), particles of various glue sizes fill the gaps on the ITB at the most upstream of image formation, and a smooth surface can be formed before the toner is printed at the next station. In particular, since the gaps are filled with glue with a small average particle size similar to that of the toner particles, if the particle size distribution of the glue is wider than that of the toner, that is, if there can be a large number of particles close to the particle size of the other side in advance, they will be less likely to mix with each other, and peel offset can be suppressed.

[0100] Next, we will explain why the peel offset improves when the average particle size difference between the toner and the glue is less than 25 μm. Figures 15A and 15B are schematic diagrams showing what size of toner particle can get into the gap of glue with a maximum average particle size of 30 μm (these are diagrams showing the ITB surface from the planar side, not the cross-sectional side).

[0101] As shown in Figure 15A, when the toner is 5 μm, the glue is 30 μm, and the average particle size difference is 25 μm, the toner will come into contact with the gaps in the glue and the powders will easily mix, which will worsen the peel offset. On the other hand, as shown in Figure 15B, when the toner is 6 μm, the glue is 30 μm, and the average particle size difference is 24 μm, it will be physically difficult for the toner to get into the gaps in the glue, and the powders will not easily mix. This makes it possible to suppress the peel offset.

[0102] Table 4 shows the relationship between the particle size difference and the peel offset.

[0103] [Table 4]

[0104] For the values ​​in Table 4, the average particle size is assumed to be a maximum of 30 μm, since the electrophotographic image formation process is used for both toner and glue. Therefore, even if the average particle size of the toner and glue changes, the figures will be similar to those in Table 4, so the situation in which they are most likely to penetrate is when the average particle size is 30 μm, which means that the situation is most severe when the average particle size difference in Table 4 is 25 μm. Therefore, it was found that peel offset can be suppressed by making the difference in average particle size smaller than 25 μm.

[0105] From the above, it became clear that in terms of the average particle size and particle size distribution of the toner and glue, the difference in average particle size between the toner and glue is less than 25 μm and the particle size distribution of the glue is wider than the particle size distribution of the toner, i.e., the half-value width is larger, which improves the suppression of peel offset.

[0106] <Summary> The advantages of the present invention are shown in Table 5.

[0107] [Table 5]

[0108] In this case, the SP value difference between the toner and the glue is 1.0 (cal / cm 3 ) 1 / 2By setting the above, the toner and the glue are less likely to dissolve in each other even in a molten state. Also, by making the viscoelastic properties of the toner and the glue different during fixing, it is possible to prevent both powders from melting all at once, and to make them less likely to dissolve in each other even when they are mixed in a molten state and a powder state. Also, by setting the difference in average particle size between the toner and the glue to less than 25 μm and making the particle size distribution of the glue larger than that of the toner, small particles of the glue can be inserted in advance into the gaps between the large particles of the glue, forming a smooth surface, making it difficult for them to mix even in a powder state. This makes it possible to effectively suppress peeling offset. Also, the image quality and gloss of the peeling surface are improved (adhesive strength is also improved in some areas).

[0109] Furthermore, by combining all of the above-mentioned configurations of SP value difference, viscoelasticity difference, average particle size and particle size distribution difference, the image quality and gloss (adhesive strength) of the release surface can be further improved in addition to the peel offset. [Explanation of symbols]

[0110] Reference Signs List 1····Image carrier (drum: 1st station), 2···Powder adhesive (glue), 3···Intermediate transfer belt (ITB), 4···Recording material (paper), 5···Fusing unit, 6···Folding unit, 7···Pressing unit, 8···Toner (Y: yellow), 9···Toner (M: magenta), 10···Toner (C: cyan), 11···Image carrier (drum: 2nd station), 12···Charging roller, 13···Cleaning container, 14···Transfer roller, 15···Secondary transfer roller, 16···Laser beam scanner, 17···Developer carrying member

Claims

1. A method for manufacturing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable state, comprising the steps of: A step of forming an unfixed composite layer on a sheet by laminating an adhesive layer formed using a powder adhesive as a surface layer on an unfixed toner image formed using a printing toner; a fixing step of heating the composite layer formed on the sheet to fix it to the sheet; a step of overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; a compression bonding step of applying pressure to the overlapping portion of the composite layer and the other composite layer under heat; having The difference in solubility parameter (SP value) between the printing toner and the powder adhesive is 1.0 (cal / cm 3 ) 1 / 2 The method for manufacturing a pressure-bonded sheet is characterized by the above.

2. 2. The method for producing a pressure-bonded sheet according to claim 1, wherein the powder adhesive contains low-density polyethylene.

3. An image forming apparatus for manufacturing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable state, comprising: a means for forming an unfixed composite layer on a sheet by laminating an adhesive layer formed using a powder adhesive as a surface layer on an unfixed toner image formed using a printing toner; a fixing means for heating the composite layer formed on the sheet to fix it to the sheet; a means for overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; and a bonding means for bonding the composite layer and the other composite layer by applying pressure under heat to the overlapping portion of the composite layer; having The difference in solubility parameter (SP value) between the printing toner and the powder adhesive is 1.0 (cal / cm 3 ) 1 / 2 The image forming apparatus according to the present invention is characterized in that

4. 4. The image forming apparatus according to claim 3, wherein said powder adhesive comprises low density polyethylene.

5. A method for manufacturing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable state, comprising the steps of: A step of forming an unfixed composite layer on a sheet by laminating an adhesive layer formed using a powder adhesive as a surface layer on an unfixed toner image formed using a printing toner; a fixing step of heating the composite layer formed on the sheet to fix it to the sheet; a step of overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; a compression bonding step of applying pressure to the overlapping portion of the composite layer and the other composite layer under heat; having The printing toner contains a wax, When the storage modulus of the printing toner at the temperature in the fixing step is G'(A1), the storage modulus of the printing toner at the temperature in the pressure bonding step is G'(A2), the storage modulus of the powder adhesive at the temperature in the fixing step is G'(B1), and the storage modulus of the powder adhesive at the temperature in the pressure bonding step is G'(B2), G'(A1)>G'(A2) G'(B1)>G'(B2) G'(B1)>G'(A1) Fulfilling A method for manufacturing a pressure-bonded sheet, characterized in that the temperature in the fixing process is a temperature between the start onset temperature and the end onset temperature of the change region due to melting in the storage modulus curve of the powder adhesive.

6. 6. The method for producing a pressure-bonded sheet according to claim 5, wherein the powder adhesive contains low-density polyethylene.

7. A method for manufacturing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable state, comprising the steps of: A step of forming an unfixed composite layer on a sheet by laminating an adhesive layer formed using a powder adhesive as a surface layer on an unfixed toner image formed using a printing toner; a fixing step of heating the composite layer formed on the sheet to fix it to the sheet; a step of overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; a compression bonding step of applying pressure to the overlapping portion of the composite layer and the other composite layer under heat; having The method for producing a pressure-bonded sheet is characterized in that the difference in average particle size between the toner and the powder adhesive is less than 25 μm, and the powder adhesive has a broader particle size distribution or a larger half-value width than the toner.

8. The method for producing a pressure-bonded sheet according to claim 7, wherein the powder adhesive contains low-density polyethylene.

9. An image forming apparatus for manufacturing a pressure-bonded sheet in which sheets are pressure-bonded to each other in a peelable state, comprising: a means for forming an unfixed composite layer on a sheet by laminating an adhesive layer formed using a powder adhesive as a surface layer on an unfixed toner image formed using a printing toner; a fixing means for heating the composite layer formed on the sheet to fix it to the sheet; a means for overlapping an area of ​​the sheet to which the composite layer is fixed with an area of ​​the sheet to which another composite layer is fixed, either on the same sheet or on a different sheet; and a bonding means for bonding the composite layer and the other composite layer by applying pressure under heat to the overlapping portion of the composite layer; having an image forming apparatus, characterized in that the difference in average particle size between said toner and said powder adhesive is less than 25 μm, and said powder adhesive has a broader particle size distribution or a larger half-value width than said toner;

10. 10. The imaging apparatus of claim 9, wherein the powder adhesive comprises low density polyethylene.

Citation Information

Patent Citations

  • Adhesive for self-sealing postcard

    JP2007045861A

  • Manufacturing method of contact bonded printed matter and adhesive application method

    JP2008149638A

  • Image forming apparatus

    JP2015176032A